2017
DOI: 10.18352/lq.10180
|View full text |Cite
|
Sign up to set email alerts
|

Research Data Services in European Academic Research Libraries

Abstract: Research data is an essential part of the scholarly record, and management of research data is increasingly seen as an important role for academic libraries. This article presents the results of a survey of directors of the Association of European Research Libraries (LIBER) academic member libraries to discover what types of research data services (RDS) are being offered by European academic research libraries and what services are planned for the future. Overall, the survey found that library directors strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
83
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(99 citation statements)
references
References 22 publications
7
83
0
9
Order By: Relevance
“…Cox et al [17] surveyed libraries in Australia, Canada, Germany, Ireland, the Netherlands, New Zealand and the United Kingdom and found an increasing maturity of data management services, although more in advisory and support roles than in technical roles. This is consistent with the results of Tenopir et al [18] who showed that European libraries tend to offer, or are planning to offer, consultative or reference research data services rather than technical or hands-on services.…”
Section: Introductionsupporting
confidence: 91%
“…Cox et al [17] surveyed libraries in Australia, Canada, Germany, Ireland, the Netherlands, New Zealand and the United Kingdom and found an increasing maturity of data management services, although more in advisory and support roles than in technical roles. This is consistent with the results of Tenopir et al [18] who showed that European libraries tend to offer, or are planning to offer, consultative or reference research data services rather than technical or hands-on services.…”
Section: Introductionsupporting
confidence: 91%
“…Note also that this analysis covered 206 universities from the 2014 Carnegie list of universities with research activity classified as 'high' or 'very high'. Tenopir et al (2017) surveyed 109 European university libraries (LIBER members) from 22 countries.…”
Section: Notesmentioning
confidence: 99%
“…While data policies have been most prolific in the UK and Australia (Shearer, 2015), they have also been found to exist at 44% and 41% of North American and European universities, respectively (Briney, Goben, & Zilinski, 2015;Tenopir et al, 2017). 1 Where policies are not yet in place, they are often planned or in the process of being established.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the website you can also find an extensive briefing paper 22 and fact sheets on the requirements of the EC for data management 23 and handling personal data.…”
Section: Openaire's Support For Open Datamentioning
confidence: 99%